2018
DOI: 10.1136/openhrt-2018-000848
|View full text |Cite|
|
Sign up to set email alerts
|

High prevalence of undiagnosed COPD among patients evaluated for suspected myocardial ischaemia

Abstract: ObjectiveChronic obstructive pulmonary disease (COPD) and coronary artery disease (CAD) are leading causes of global morbidity and mortality. Despite the well-known comorbidity between COPD and CAD, the presence of COPD may be overlooked in patients undergoing coronary evaluation. We aimed to assess the prevalence of undiagnosed COPD among outpatients evaluated due to suspected myocardial ischemia.MethodsAmong 500 outpatients who were referred to myocardial perfusion imaging due to suspected stable myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Patients may not be motivated to seek medical help due to a lack of understanding of the disease itself, feelings of guilt and stigma associated with a COPD diagnosis, 101 , 102 the feeling that it is “too late” to change or simply due to ignoring symptoms and/or attributing them to another cause. 103 , 104 Greater public awareness and knowledge of the condition and the possibilities for its treatment are needed to counter these issues. Implementing behavior-targeted interventions with the aim of improving physical activity should also be considered as physical activity is often significantly reduced in COPD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Patients may not be motivated to seek medical help due to a lack of understanding of the disease itself, feelings of guilt and stigma associated with a COPD diagnosis, 101 , 102 the feeling that it is “too late” to change or simply due to ignoring symptoms and/or attributing them to another cause. 103 , 104 Greater public awareness and knowledge of the condition and the possibilities for its treatment are needed to counter these issues. Implementing behavior-targeted interventions with the aim of improving physical activity should also be considered as physical activity is often significantly reduced in COPD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Myocardial perfusion imaging (MPI) was performed and interpreted according to current guidelines [ 43 , 44 ] as a part of routine clinical investigation at the Department of Clinical Physiology and Nuclear Medicine at Skåne University Hospital in Malmö, Sweden. The MPI protocol, which has been previously described in detail [ 42 ], included provocation with either exercise on a bicycle or pharmacological provocation with adenosine or regadenosone, after which 99m Tc-tetrofosmin was injected, and Single Photon Emission Computed Tomography (SPECT) Images were obtained using a dual-head gamma camera (Siemens AG Medical Solutions, Erlangen, Germany). From March 2015 the SPECT acquisition was complemented by a low dose CT scan for attenuation correction.…”
Section: Methodsmentioning
confidence: 99%
“…The BiG CaPPS cohort. Data were collected from the Biomarkers and Genetics Cardio-Pulmonary Physiology Study (BiG CaPPS)-cohort, which has been previously described in detail [42]. In short, the BiG CaPPS cohort consists of 500 outpatients with suspected stable myocardial ischemia, all of whom had been clinically referred by a physician to myocardial perfusion imaging (MPI) during 2014-2017.…”
Section: Study Populationmentioning
confidence: 99%
“…16,25 This association has been explained by common risk factors, most notably smoking. 25,26 We also found that in the PiZZ individuals, COPD was an independent risk factor for developing IHD both in PiZZ subjects and in controls. However, smoking was an independent risk factor for developing IHD only in the controls, not in the PiZZ subjects, which is difficult to explain.…”
Section: Discussionmentioning
confidence: 54%